Perpaduan Budaya dalam Modernisasi Busana Muslimah di Yogyakarta, 1950-1980 - Ahsan, Muhammad Fikri Fikri (Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
The entry of post-independence globalization also influenced the Muslim fashion models in Yogyakarta. This phenomenon is interesting to see how Muslim women adjust their appearance to keep looking polite in the midst of the onslaught of incoming western fashion trends. Specifically, this study will discuss the cultural fusion in the modernization of Muslim women's clothing in Yogyakarta in 1950-1990. The purpose of this study is to reveal how the original appearance of Muslim women in Yogyakarta before the entry of Western culture, then find out how the results of the integration of Western clothing with Muslim women's clothing, as well as explain what are the factors behind Muslim women in Yogyakarta in modernizing their clothing. This research data was collected from various newspapers published in Indonesia, especially Yogyakarta and several relevant scientific papers. The result of this research is the imitation of appearance style by Muslim women in Yogyakarta with the addition of accessories in their clothing. In addition, the integration of two cultural elements in Muslim women's clothing in Yogyakarta which then gave birth to a new style of clothing, namely overalls and headscarves that look more modern. Through this research, it is also known the factors that cause the fusion of these cultures such as the factors of print media and the Iranian revolution in 1979 which became a turning point in the rise of Islam in Indonesia.